Issues and developments in international trade policy : Occasional Paper No 63 - International Monetary Fund; Kelly, Margaret R. (Washington, D.C. : International Monetary Fund, 1988)
This study provides an overview of trade policy trend, major issue facing the multilateral trading system and the prospects for liberalization.
Bibliography: p. 169-173.
ijb, 18/01/2019
Loans
Keywords: International trade; Commercial policy